The contribution of non-primary caregivers in early stimulation in Kenya and Uganda: Implications for ECD parenting programs in low- and middle-income countries - Eunsoo Timothy Kim; Darcy Strouse; Sandra Sandoval; Lukiya Kibone; Damaris Wambua; Michela Profeta (PLoS ONE, 2025)
Parenting programs have primarily focused on supporting mothers with knowledge and practice of responsive caregiving. However, the role of non-primary caregivers such as grandparents, aunts, and older siblings has not been adequately addressed in programming. Using ChildFund International’s programmatic data from Kenya and Uganda, this cross-sectional study examined the extent to which children aged 0–5 years were left in the care of non-primary caregivers in the household and whether the primary caregivers’ absence was associated with engagement by non-primary caregivers. We found that a considerable proportion of children aged 0–5 years in Kenya and Uganda were entrusted in the care of non-primary caregivers for at least 3 days or more during the week. Yet, the primary caregivers’ absence was not consistently associated with greater engagement by fathers and other members of the household. Our findings call for parenting programs to consider adopting a holistic and contextualized approach where all involved caregivers are intentionally targeted rather than focusing just on the identified primary caregiver alone.